2008
DOI: 10.1016/j.micres.2006.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Citrus sinensis (L.) Osbeck epicarp essential oil on growth and morphogenesis of Aspergillus niger (L.) Van Tieghem

Abstract: Essential oils from different plant parts are known for their antimicrobial activity but the antifungal effects of essential oil from Citrus sinensis (L.) Osbeck epicarp on growth and morphogenesis of Aspergillus niger has not been observed so far. The mycelial growth was inhibited at 2.5 and 3.0 microg/ml of oil in Potato Dextrose Broth and Agar medium, respectively. These concentrations were fungicidal under the test conditions. The fungitoxicity of oil did not change even at exposure to 100 degrees C and au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
175
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(195 citation statements)
references
References 14 publications
15
175
1
4
Order By: Relevance
“…The other metabolic activity indicators showed negligible changes. loss of rigidity, and integrity of the hypha resulting in the collapse and death of the mycelium, similar to that reported by Sharma and Tripathi (2006). Such possibility is suggested by the inhibition of amylase activity (95%) of the F. graminearum 702-01 stock isolated from wheat.…”
Section: Resultssupporting
confidence: 83%
“…The other metabolic activity indicators showed negligible changes. loss of rigidity, and integrity of the hypha resulting in the collapse and death of the mycelium, similar to that reported by Sharma and Tripathi (2006). Such possibility is suggested by the inhibition of amylase activity (95%) of the F. graminearum 702-01 stock isolated from wheat.…”
Section: Resultssupporting
confidence: 83%
“…This difference in antifungal activity between essential oils from plants of the same species can be explained by the chemotype (chemical composition), geographical region of plant collection, age of plant, extraction method of oils, method used to assess the antifungal activity or by the intra or inter species differences (Samaranayake et al, 1995;Cruz et al, 2007;Maksimovic et al, 2008). Sharma & Tripathi (2008) have shown that the antifungal activity of essential oils is better evaluated in liquid than in solid media, since in the latter, the hydrophobic nature of the majority of essential oil components hamper uniform diffusion of these substances through the agar medium (de Cerqueira et al, 2007). We used the standard microdilution methods M38-A and AFST-EUCAST for the evaluation of antifungal susceptibility of filamentous fungi and yeasts, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Sharma and Tripathi (2008) have shown that the antifungal activity of essential oils can be more effectively evaluated in liquid rather than in solid media, since in the latter, oil diffusion may not be appropriate. In this study, the standard methods of microdilution for the evaluation of antifungal susceptibility to drugs were used.…”
Section: Discussionmentioning
confidence: 99%
“…Hayes and Markovic (2002) showed that Backhousia citriodora essential oil, with a 92% composition of citral, was active against C. albicans and Aspergillus niger with MICs comparable to commercial citral. Recently, Sharma and Tripathi (2008) determined, through an agar diffusion method, a MIC value of 0.3 µg/mL against A. niger for a Citrus sinensis essential oil, which has a limonene concentration of 87%. Linalool and linalool-rich essential oils from Croton cajucara are active against C. albicans, with MIC values of 0.7 µg/mL and 13.4 µg/mL, respectively (Alviano et al 2005).…”
Section: Discussionmentioning
confidence: 99%